Analysis of cell-associated DENV RNA by oligo(dT) primed 5 capture scRNAseq - Mark Sanborn; Tao Li; Kaitlin Victor; Hayden Siegfried; Christian Fung; Alan L. Rothman; Anon Srikiatkhachorn; Stefan Fernandez; Damon Ellison; Richard G. Jarman; Heather Friberg; Irina Maljkovic Berry; et al. (My University, 2020)
ABSTRACT Dengue is one of the most widespread vector-borne viral diseases in the world. However, the size, heterogeneity, and temporal dynamics of the cell-associated viral reservoir during acute dengue virus (DENV) infection remains unclear. In this study, we analyzed cells infected in vitro with DENV and PBMC from an individual experiencing a natural DENV infection utilizing 5’ capture single cell RNA sequencing (scRNAseq). Both positive- and negative-sense DENV RNA was detected in reactions containing either an oligo(dT) primer alone, or in reactions supplemented with a DENV-specific primer. The addition of a DENV-specific primer did not increase the total amount of DENV RNA captured or the fraction of cells identified as containing DENV RNA. However, inclusion of a DENV-specific cDNA primer did increase the viral genome coverage immediately 5’ to the primer binding site. Furthermore, while the majority of intracellular DENV sequence captured in this analysis mapped to the 5’ end of the viral genome, distinct patterns of enhanced coverage within the DENV polyprotein coding region were observed. The 5’ capture scRNAseq analysis of PBMC not only recapitulated previously published reports by detecting virally infected memory and naïve B cells, but also identified cell-associated genomic variants not observed in contemporaneous serum samples. These results demonstrate that oligo(dT) primed 5’ capture scRNAseq can detect DENV RNA and quantify virus-infected cells in physiologically relevant conditions, and provides insight into viral sequence variability within infected cells. IMPORTANCE Dengue is one of the most widespread vector-borne viral diseases in the world. However, it is still unclear which cells harbor virus during DENV infection, and how viral reservoirs in serum and infected cells are related. These results demonstrate for the first time that intracellular DENV RNA can be identified and infected cells quantified by 5’ capture scRNAseq. This strategy provides a significantly greater throughput and higher sensitivity than previously published methods and has the potential to provide additional information on the genomic heterogeneity of intracellular DENV RNA.
Keywords: Primer (cosmetics); Mosquito-borne diseases and control